Hand hygiene monitoring technology: A descriptive study of ethics and acceptance in nursing. (March 2022) - Meng, Michael; Seidlein, Anna-Henrikje; Kugler, Christiane
Background: Nosocomial infections represent a serious challenge for healthcare systems worldwide. Adherence to hand hygiene plays a major role in infection prevention and control. These adherence rates can be improved through behaviour tracking innovations. This requires the systems to be widely implemented and accepted. Therefore, both a systematic analysis of the normative issues related and the evaluation of technology acceptance are equally important. Objectives: To explore and describe relevant aspects regarding the acceptance of technology and ethical implications using a tracking device to measure and improve adherence to hand hygiene. Research design: A quantitative study with a descriptive design was performed. Participants and research context: A total of 75 questionnaires were collected in three hospitals in Germany. Acceptance of technology was measured with n = 60 participants (n = 50 nurses; n = 9 physicians; n = 1 not disclosed) and ethical assessment with n = 15 participants (nurses only). Ethical considerations: Ethical approval for this study was obtained from the institutional review board. Findings: The acceptance of technologies improving hygiene in general was good (median = 80.5, interquartile range = 28, range: 0–100). The experience with technologies in general (median = 48.5, interquartile range = 57, range: 0–100) and the acceptance of the specific technology (mean = 82.23, standard deviation = 15.16 (range: 23–138)) was moderate. There was a significant positive correlation between the acceptance and experience of technology in general ( r = 0.217, p = .025). Ethical concerns played a minor role. The need for practical support was a key topic. Discussion: Study participants accepted technologies improving hygiene; however, the specific device implemented was only moderately accepted. This creates specific opportunities in the implementation process for higher later acceptance. More practical support and an increase in experience may create opportunities for device implementation with high acceptance and low ethical concerns. Conclusion: Study results indicate a vast potential for improving the implementation process of hand hygiene technologies. Ethical concerns in this study did not seem to be a relevant barrier for successful implementation of hand hygiene technologies.